Tissue engineering in flexor tendon surgery: current state and future advances. (January 2014) - Galvez, M. G.; Crowe, C.; Farnebo, S.; Chang, J.
Tissue engineering of flexor tendons addresses a challenge often faced by hand surgeons: the restoration of function and improvement of healing with a limited supply of donor tendons. Creating an engineered tendon construct is dependent upon understanding the normal healing mechanisms of the tendon and tendon sheath. The production of a tendon construct includes: creating a three-dimensional scaffold; seeding cells within the scaffold; encouraging cellular growth within the scaffold while maintaining a gliding surface; and finally ensuring mechanical strength. An effective construct incorporates these factors in its design, with the ultimate goal of creating tendon substitutes that are readily available to the reconstructive hand surgeon.